Morphometrical and Gross anatomical Study on the Sternum of Blue and Gold winged Macaw (Ara ararauna) - Yousuf Dar (Indian Journal of Veterinary Anatomy, 2022)
The present study was conducted on the sternum of blue and gold winged macaw.The sternum of macawconsisted of rostrum (manubrium sterni), body (corpus sterni) and sternal crest (crista sterni). The manubriumsterni was hook like, flattened from side to side. The corpus sterni was long 76.35 mm quadrilateral with concavedorsal and convex ventral surface. It presented four borders; anterior, posterior and two lateral borders.The widthof sternum between the craniolateral process was 33.89 mm and the width at caudal aspect was 49.21mm. Thewidth of sternum at the anterior aspect was less than the width at the posterior aspect.In the present study thedorsal surface was concave and showed a groove in the center extending from behind the cranial border up todistal third. The concavity was more in cranial half and nearly flat in caudal half.Numerous foramina were presenton the anterior two third of the dorsal surface. The ventral surface was convex and presented a large, boat shapedsternal crest along its median line.The sternal crest was located at the center of the ventral surface of corpus sterni.The sternal crest was boat shaped and 89.05 mm in length. The height of the sternal crest along with the cranialborder was 27.93 mm. Therefore, it was concluded that the sternum of blue winged macaw was similar to gooseand pigeon and hence the morphometry and morphology of sternum is suitable for the flying of bird.